Damage detection in composite materials structures under variable loads conditions by using fiber Bragg gratings and principal component analysis, involving new unfolding and scaling methods. (July 2015) - Sierra-Pérez, Julián; Güemes, Alfredo; Mujica, Luis E; Ruiz, Magda
An innovative methodology based on the use of fiber Bragg gratings as strain sensors and strain field pattern recognition is proposed for damage detection in composite materials structures. The strain field pattern recognition technique is based on principal component analysis. Damage indices ( T 2 and Q ) and detection thresholds are presented. New techniques for unfolding and scaling tridimensional matrices arrays obtained from structures working under variable load conditions are presented.